Hong Kong and the Cold War Anglo-American relations 1949-1957 - Mark, Chi-Kwan (Oxford historical monographs., 2004)
After 1949, the British Empire in Hong Kong was more vulnerable than it appeared to be. This scholarly study explores the interactions of British and US policies towards Hong Kong, and reveals the dynamics of the Anglo-American alliance and the dilemmas of small allies in the global Cold War.